Electrochemical Kinetic Study of Calotropis procera - SINGH, P.K.; AGRAWAL, RAMA; KHAN, M.U.; K. NIGAM, SUNIL; KHAN, SHAHNAJ (Asian Journal of Chemistry, 2010)
Electrochemical kinetic study of Calotropis procera (verna: madar) of the family Asclepiadaceae has been carried. out, with electrode pair Ag-Zn in three different seasons. The reaction showed first to zero order rate dependence and also indicated complex nature of oscillatory reaction occurring in the system, obeying redox process. Various amino acids were analyzed. The zwitter ions of proteins present in the sap are fully responsible for flow of current due to charge transfer. A plausible mechanism based on rate law was proposed and thermodynamic parameters evaluated.